Tingkat Keramahan Lingkungan Alat Tangkap Purse Seine di Pelabuhan Perikanan Samudera (PPS) Belawan Sumatera Utara - Megawati Megawati; Exist Saraswati; M Tajuddin Noor (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2026)
Indonesia is the largest archipelagic country in the world, Belawan Ocean Fishing Port is one of the largest fishing ports in WPP-NRI 571, strategic position because it is located between the waters of the East Coast and the South China Sea. The status of fish resource utilization in Belawan Ocean Fishing Port which has been fully exploited makes a study to analyze the level of fishing gear use in Belawan Ocean Fishing Port. This study aims to determine the level of environmental friendliness of purse seine fishing gear. This study was conducted at Belawan Ocean Fishing Port in November-December 2025. The research method used was a survey method, direct observation and interviews using a questionnaire. The sample used was 30 respondents. The analysis of the level of environmental friendliness of fishing gear was carried out in accordance with the criteria of 9 Code of Conduct for Responsible Fisheries (CCRF). The results of the calculation of the environmental friendliness score were 30.2 out of a total of 908 points for the level of friendliness of purse seine fishing gear at Belawan Ocean Fishing Port, and this fishing method is categorized as a very environmentally friendly fishing gear.